Sehat Card Plus in Khyber Pakhtunkhwa: Confronting challenges, strengthening governance, ensuring financial sustainability - Sameen Siddiqi; Shifa Salman Habib; Waqas Hameed; Asma Altaf Hussain Merchant; Junaid Ur Rehman Siddiqui; Kiran Sohail Azeemi; Adil Haider, Soonman Kwon; Viroj Tangcharoensathien (Journal of the Pakistan Medical Association, 2024)
Objective: To conduct an in-depth policy analysis of the Sehat Card Plus (SCP), focussing on its governance, financing structures, achievements, and long-term sustainability. Methods:A three-tiered framework was employed. At the micro-level, over 4,000 households were surveyed; at the mesolevel, readiness assessments were conducted at 38 empanelled hospitals; and at the macro-level, a policy and strategic review of the SCP was conducted. The policy review examined (i) programme governance and coordination, including thirdparty administration by SLIC; (ii) current status of legislative and regulatory aspects; (iii) financing trends and sustainability; (iv) service delivery mechanisms, including beneficiary enrollment, empanellment and reimbursement mechanisms; and (v) monitoring and evaluation systems. A mixed-methods approach was used, combining literature review, technical reports, and budgetary documents with in-depth interviews conducted with provincial and federal officials, health system experts, and stakeholders. Data from interviews was collected between October and November 2022 underwent thematic deductive analysis. Results: Six thematic areas were identified: (i) Governance: Strong legislative commitment through the UHC Bill 2022, but with limited citizen representation in decision-making bodies; (ii) Organizational arrangements: Limited staff and dependence on SLIC limit monitoring and strategic management; (iii) Financing: Unplanned expansion challenges financial sustainability in economic crisis, as SCP is fully funded by provincial revenues; (iv) Service purchasing: State Life Insurance Corporation (SLIC) manages hospital empanellment and claims processing, though lack of involvement of health authorities; (v) Monitoring & evaluation: Independent monitoring systems are needed for transparency and quality assurance (vi) Communication and User Satisfaction : Beneficiary engagement and feedback mechanisms in SCP need improvement. Conclusion: SCP has expanded inpatient care and improved financial protection, but challenges remain in quality, financial sustainability, and equity, crucial for achieving UHC in Pakistan. Keywords: Universal Health Coverage (UHC), Sehat Card Plus (SCP), Khyber, Pakhtunkhwa (KP), Publicly Funded Health Insurance, Social Health, Protection Initiative (SHPI).